Compositional engineering of phase-stable and highly efficient deep-red emitting phosphor for advanced plant lighting systems - Jianwei Qiao; Dehong Li; Qiufeng Shi; Haijie Guo; Ping Huang; Lei Wang (Light: Science & Applications)
Abstract Inorganic luminescent materials hold great promise for optoelectronic device applications, yet the limited efficiency and poor thermal stability of oxide-based deep-red emitting phosphors hinder the advancement of plant lighting technologies. Herein, a simple compositional engineering strategy is proposed to stabilize the phase, boost external quantum efficiency (EQE) and enhance thermal stability. The chemical modification of the PO4 tetrahedron in NaMgPO4:Eu by incorporating SiO4 lowers the formation energy, leading to the generation of pure olivine phase and increasing the EQE from 27% to 52%, setting a record for oxide deep-red phosphors. In parallel, the introduced deep defect level improves thermal stability at 150 °C from 62.5% to 85.4%. Besides, the excitation and emission peaks shifted to 440 nm and 675 nm, respectively, aligning precisely with the specific spectral absorption requirements of plant phytochromes. Moreover, the luminescent intensity showed nearly no decay after being exposed to 80% relative humidity and 80 oC for 6 h, and the pc-LED utilizing Na1.06MgP0.94Si0.06O4:Eu achieves a high output power of 780 mW at 300 mA. Our research demonstrates a facile method for optimizing the performance of inorganic luminescent materials and provides alternative solutions for low-cost plant lighting.